từ pt trên bạn pt đa thức thành nhân tử được (a+b+c)(a^2-ab+b^2-ac-bc+c^2)=0
mà a+b+c khác 0 nên a^2-ab+b^2-ac-bc+c^2=0
2(a^2-ab+b^2-ac-bc+c^2)=0
(a-b)^2+(a-c)^2+(b-c)^2=0
suy ra a=b=c
suy ra A=1/3
\(a^3+b^3+c^3=3abc\Leftrightarrow a^3+b^3+c^3-3abc=0\)
<=>\(\left(a+b+c\right)\left(a^2+b^2+c^2-ab-bc-ca\right)=0\)
mà \(a+b+c\ne0\Rightarrow a^2+b^2+c^2-ab-bc-ca=0\)<=>\(a^2+b^2+c^2=ab+bc+ca\)
=>\(A=\frac{a^2+b^2+c^2}{\left(a+b+c\right)^2}=\frac{a^2+b^2+c^2}{a^2+b^2+c^2+2\left(ab+bc+ca\right)}=\frac{a^2+b^2+c^2}{a^2+b^2+c^2+2\left(a^2+b^2+c^2\right)}\)
\(=\frac{a^2+b^2+c^2}{3\left(a^2+b^2+c^2\right)}=\frac{1}{3}\)